A New History of the Gdańsk/Danzig Organ Tablature - Marcin Szelest (Muzyka)
The article presents new findings concerning the so-called Gdańsk/Danzig Organ Tablature from the late sixteenth century. They include a codicological description of the manuscript in which it was recorded (Gdańsk, State Archive, shelf mark 300,R/Vv,123) and recognition of the manuscript’s contents; distinguishing the scribes; identification of the owner of the book and the scribe of the music; a history of the music section of the manuscript; an analysis of groups of works, their function and features of their notation. In the last part, working hypotheses are proposed concerning i.a. the authorship of the compositions, intended to outline the perspectives for future research.